Sexism in Haya Language Personal Names Selection (JULACE: Journal of the University of Namibia Language Centre, 2018)
This paper examines sexism in naming focussing on the meaning of Haya personal names used in Haya community of North Western Tanzania. It is based on the assumption that some conscious personal names are selected in favour of men. This disparity is well examined by using the Critical Discourse Analysis approach. The paper presents field data from Bukoba Rural district in Kagera Region. The results reveal that meanings of male names were associated with high worthwhile the meanings of female names were associated with low worth. This was justified by the point that Haya male names referred to male as a saviour and helper of the family and society, a strong person, a fighter, a winner, rich and famous person while female names were connected with love, attraction, comfort, soothes and parents disappointment for having a baby girl. The study found that names of female children indicate an important argument that parents considerfemale child as a burden and liability. Generally, it was observed that selection of some Haya personal names was done in discriminatory manner that need an urgent emphasis on the value of names of girls in families and society in general.
Keywords: sexism; personal names; Haya language; name selection